2018
DOI: 10.1177/0197918318769313
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Ties: The Reproduction of Legal Violence within Mixed-Status Intimate Partners, Relatives, and Friends

Abstract: This article introduces the concept of toxic ties to analyze how relationships between documented and undocumented people are impacted by governmental policies that sanction legal violence and unevenly distribute legal rights, protections, and benefits. Toxic ties are relationships in which a documented person abuses, exploits, or demeans his or her undocumented partners, relatives, or friends. Drawing on interviews with undocumented and US-born young adults in southern California, the article shows that as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 20 publications
1
32
0
Order By: Relevance
“…Furthermore, structural violence (Farmer 2004; Galtung 1969), i.e., “the methodical and often subtle processes through which social structures disadvantage and harm certain groups of people” (Hodgetts et al 2014, 3), is reproduced and normalized in everyday interactions, “essentially cementing the disadvantage initiated by larger macro- and meso-level forces” (Smith 2010, 4). In this regard, interpersonal relations also play a role in shaming, stigma , and exploitation (e.g., Del Real 2019; Levine 2013). For example, family and friends can be judgmental about a person’s welfare reliance rather than supportive, thereby replicating and normalizing state and public discourse about the causes of poverty.…”
Section: Network Effects and Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, structural violence (Farmer 2004; Galtung 1969), i.e., “the methodical and often subtle processes through which social structures disadvantage and harm certain groups of people” (Hodgetts et al 2014, 3), is reproduced and normalized in everyday interactions, “essentially cementing the disadvantage initiated by larger macro- and meso-level forces” (Smith 2010, 4). In this regard, interpersonal relations also play a role in shaming, stigma , and exploitation (e.g., Del Real 2019; Levine 2013). For example, family and friends can be judgmental about a person’s welfare reliance rather than supportive, thereby replicating and normalizing state and public discourse about the causes of poverty.…”
Section: Network Effects and Well-beingmentioning
confidence: 99%
“…Similarly, a New Zealand study observed that the poor perceived case workers as abusive, disrespectful, disinterested, and judgmental, scrutinizing every aspect of a person’s life in exchange for social support (Hodgetts et al 2014). Finally, Del Real (2019) reported how low-income undocumented immigrants in Southern California had what she called “toxic ties” with documented partners, relatives, and friends, i.e., relationships that are intentionally or unintentionally exploitative, demeaning, or abusive as a result of the power differential in these relationships (see also Offer and Fischer [2018] for research on difficult ties). They could be reported by them, robbed without the legal means to press charges, or otherwise exploited.…”
Section: Social Network and Povertymentioning
confidence: 99%
“…However, this assumption does not always hold, and other research reveals that economic inequality fragments immigrants' networks (Menjívar 2000) and even facilitates exploitation (Cranford 2005;Rosales 2013). Furthermore, the uneven distribution of legal rights between undocumented and documented people normalizes subtle forms of exploitation that reproduce state legal violence (Menjívar and Abrego 2012) within immigrants' intimate ties (Del Real 2018). By focusing on social mechanismsmalfunctioning technology, exclusion from coethnic supports, a stigmatizing labelthat generate extended punishment within the spaces of government, community, and self, I argue that post-detention EM surveillance erodes immigrants' main source of support: their social ties.…”
mentioning
confidence: 95%
“…Recent changes in immigration policy have made it difficult for undocumented immigrants to adjust their status and have extended enforcement efforts from the border to the nation's interior, which further heighten its profound impacts (Gonzales & Raphael 2017). The children of undocumented immigrants grow up amid an increasingly harsh context of limitation and intense enforcement efforts that have sown fear and anxiety within large, settled immigrant populations (Del Real 2018, Garcia 2018, Lopez et al 2017. Recent studies have provided an important window through which to understand the influence of undocumented status on the incorporation of undocumented immigrants and their native-born children as well as their foreign-born undocumented children (Abrego 2006;Bean et al 2011, Dreby 2010, Gonzales 2016, Yoshikawa & Kalil 2011).…”
Section: The Limitations Of Undocumented Statusmentioning
confidence: 99%